Contested Organ Harvesting from the Newly Deceased: First Person Assent, Presumed Consent, and Familial Authority. Issue 5 (16th September 2019) - Cherry, Mark J
Abstract: Organ procurement policy from the recently deceased recasts families into gatekeepers of a scarce medical resource. To the frustration of organ procurement teams, families do not always authorize organ donation. As a result, efforts to increase the number of organs available for transplantation often seek to limit the authority of families to refuse organ retrieval. For example, in some locales if a deceased family member has satisfied the legal conditions for first-person prior assent, a much looser and easier standard to satisfy than informed consent, organ retrieval may proceed despite the family's objections. Some countries have replaced voluntary consent to organ donation with forms of organ conscription. Often referred to under the misnomer "presumed consent, " such policies legalize the harvesting of organs at death, unless individuals exercise official options to opt out. As this article explores, however, there are good grounds for affirming the authority of the family to consent to or to deny organ donation on behalf of recently deceased family members, as well as to reject first-person assent and "presumed consent" policies of organ procurement. Insofar as individuals have failed clearly and competently to provide informed consent to organ donation, moral authorization for the use of the person and his body ought to be grounded on the foundational authority of the family, rather than the state's supposed interests in obtaining organs for transplantation.